Muscle Strength Thresholds for the Detection of Cardiometabolic Risk Among Colombian Children and Adolescents: The Fuprecol Study - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible